Adverse effect profile with low-dose methotrexate therapy in patients suffering with rheumatic diseases - Parimi, Vijaya; Mirza, Mehdi; Bandaru, Rajiv; Surapareddy, Bhavana; Bala, Sudha; Rakesh, Srigaari (National journal of physiology, pharmacy and pharmacology, 2024)
Background: Methotrexate (MTX) is the anchor drug for the management of many systemic inflammatory diseases. High-dose MTX is associated with various toxicities which may lead to drug discontinuation or interruption of therapy. Low-dose MTX is widely used for treating various systemic autoimmune diseases and is considered relatively safe. Aims and Objectives: In this study, we describe the clinical features and factors affecting adverse effects of low-dose MTX in a large cohort of patients with autoimmune rheumatic diseases (AIRDs) from a tertiary health center in South India. Materials and Methods: This was a retrospective analysis wherein we aimed to characterize the clinical features seen in and factors associated with adverse effects due to low-dose MTX. We reviewed the medical records of patients who were receiving MTX for their underlying AIRD from the Department of Clinical Immunology and Rheumatology and General Medicine. Inclusion: Patients with AIRDs being treated with MTX, who suffered from adverse events. Excluded: Patients on other csDMARDs and bDMARDs. Clinical profile, indications of therapy, dose of MTX, adverse effects, and deranged laboratory parameters were noted. Results: A total of 815 subjects using MTX were identified over a period of 6 months duration (n = 713 (87%) females). Underlying autoimmune conditions included rheumatoid arthritis (n = 675, 82.8%). The most common adverse event noted was hair loss (7.7%), followed by nausea (3.9%). Cytopenia and transaminitis were noted in 1.6% and 2.2%, respectively. Higher incidence of adverse events was seen in those without folic acid intake (81.2%; P = 0.0001). Conclusion: Low-dose MTX, although causes mild adverse effects and has the potential to cause life-threatening adverse events like cytopenia, is usually well tolerated. Identification of toxicities early improves the outcomes of patient care. Folate supplementation ameliorates side effects.